ICSID arbitrators: actors in the global fight against corruption (2020)
Corruption is a cancer that hinders economic development, especially when foreign investors corrupt public officials in developing States. Arbitrators face many legal challenges when dealing with corruption allegations. Particularly, under the ICSID Convention, which not only establishes the procedural framework for arbitration but also aims to promote economic development through foreign investment. The subject matter of this policy report is the analysis of ICSID arbitration cases involving allegations of corruption. The report concludes by identifying what the major trends in the analysis of corruption allegations under ICSID arbitration are.